Faktor Yang Berpengaruh Terhadap Kecelakaan Kerja Pada Operator Truk Di Terminal Petikemas New Makassar (Window of Public Health Journal, 2025)
Work accidents are incidents that occur to workers and are closely related to work so that workers complain of pain due to illnesses suffered and arise while working or incidents that occur when leaving work from home to the workplace and returning home accompanied by injuries, physical abnormalities, disabilities, and even death. This study aims to determine the factors that influence the occurrence of work accidents in Truck Operators at the New Makassar Container Terminal. This type of research uses a quantitative method with a cross-sectional study design with a population of 500 workers and a sample of 90 workers; the technique for determining the number of samples using the Lemeshow formula. Data analysis was done univariately and bivariately using the chi-square test to determine the influential variables. The results of this study obtained a p-value of work period with work accidents of 0.816 and a p-value of supervision with work accidents of 0.251. This study concludes that there are no variables that influence work accidents. The suggestion from this study is that it is hoped that the company, especially supervisors in the field, will be more assertive in reprimanding truck operators who are negligent in their work, especially in the unsafe actions of workers.